Stopping and storing light pulses within a fiber optic ring resonator - Suhailin, Fariza H.; Ali, Jalil; Yupapin, Preecha Promphan; Fujii, Yusaku; Ahmad, Harith; Harun, Sulaiman Wadi (Optical Society of America, 2009)
A simple all optical system for stopping and storing light pulses is demonstrated. The system consists of an erbium-doped fiber amplifier (EDFA), a semiconductor optical amplifier (SOA), and a fiber ring resonator. The results show that the multisoliton generation with a free spectrum range of 2.4 nm and a pulse spectral width of 0.96 nm is achieved. The memory time of 15 min and the maximum soliton output power of 5.94 dBm are noted, respectively. This means that light pulses can be trapped, i.e., stopped optically within the fiber ring resonator.